(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In Ayurveda, Arsha is described in Ashta Mahagada also called as the Eight grave diseases as per Acharya Sushruta. The population has a high rate of Arsha, with 39.93% having Grade I hemorrhoids, followed by Grade II, III, and IV hemorrhoids. Overall prevalence is stated to be 4.4% worldwide. The conservative treatment for piles is to use laxatives, a high-fiber diet, and local ointments, among other things. Study of Ayurvedic literatures reveal that the disease Arsha has been widely described in the classics which simulate the clinical picture of haemorrhoids at modern parlance. Although, haemorrhoids are associated with definite local organic changes, Lokhart Mummery et.al, believe that the frequent occurrence of the condition in men, in contrast to lower animals is the result of erect posture. Mild to profuse type of bleeding during defecation in some cases along with mucus discharge, pain and protrusion of pile mass on complete development of the disease, are prominent diagnostic features of Arsha. These signs and symptoms are almost same as described for the disease haemorrhoids. The medical knowledge has been advanced to a great extent in all spheres of medical practices, but the disease piles still seem to be a challenge to the medical professionals, as the available medicinal treatment is only palliative and not a curative measure.